(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article analyzes the development of the digital economy. The essence of the scenario of digital transformation of the economy has been studied. With the help of the rating system for the development of the digital economy and e-government, as well as the interdepartmental mechanism for its implementation, an analysis of the current state of the digital transformation of the republic’s industries was carried out. A comparative analysis of digitization with foreign countries was carried out.